2021
DOI: 10.1136/sextrans-2020-054791
|View full text |Cite
|
Sign up to set email alerts
|

HIV non-occupational postexposure prophylaxis (nPEP) usage among five key populations in China

Abstract: ObjectivesTo examine the feasibility of non-occupational postexposure prophylaxis (nPEP) as a national strategy for HIV prevention in China, we investigated nPEP usage and related sociodemographic and behavioural factors among five key populations at high risk of contracting HIV.MethodsWe conducted a cross-sectional study among five key populations from November 2018 to September 2019 in China using convenience sampling to recruit participants aged ≥18 years, self-reporting HIV status as either negative or unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
0
6
1
Order By: Relevance
“…In this study, 97.0% (523/539) of PEP users presumably completed the full 28-day course of medication, and this rate was higher than the completion rates in 2 other Chinese studies, where 86% [47] and 92.2% [41] of PEP users completed the 28-day course of medication, respectively. Furthermore, a systematic review and meta-analysis of 97 studies worldwide showed an even lower rate of PEP completion (67.2%; 95% CI 59.5%-74.9%) [48].…”
Section: Principal Findingscontrasting
confidence: 68%
“…In this study, 97.0% (523/539) of PEP users presumably completed the full 28-day course of medication, and this rate was higher than the completion rates in 2 other Chinese studies, where 86% [47] and 92.2% [41] of PEP users completed the 28-day course of medication, respectively. Furthermore, a systematic review and meta-analysis of 97 studies worldwide showed an even lower rate of PEP completion (67.2%; 95% CI 59.5%-74.9%) [48].…”
Section: Principal Findingscontrasting
confidence: 68%
“…In addition, we found that the decline in PEP prescriptions during the COVID-19 pandemic occurred primarily in people aged 50 years and younger, which may be because older adults are less adaptive to this unconventional and underutilized HIV prevention measure in China. A study in ten Chinese cities 36 found people aged 50-64 years were less likely to use non-occupational postexposure prophylaxis (nPEP) (OR 0·179, 95% CI 0·036-0·894) compared to those aged 18-34 years, although it was not statistically significant for those aged 65 years and older (OR 0·232, 95% CI 0·014-3·975). As travel restrictions were attenuated and social life gradually returned to normal, people may resume their previous sexual frequency and risk.…”
Section: Discussionmentioning
confidence: 99%
“…High-risk behaviors during them such as unprotected sex, multiple sex partners and temporary partner [ 35 – 37 ] still occurred due to the separation of knowledge, belief and practice. And this group is harder to reach for CDC staffs, some people reached the populations through collaboration with gay-friendly CBO [ 38 ].Non-occupational postexposure prophylaxis (nPEP) was an effective means of prevention [ 39 ], but the cost was high for students. Treatment and care interventions are still effective interventions for these populations.…”
Section: Discussionmentioning
confidence: 99%